2003
DOI: 10.1121/1.1604122
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear compression estimates from measurements of distortion-product otoacoustic emissions

Abstract: Evidence of the compressive growth of basilar-membrane displacement can be seen in distortion-product otoacoustic emission (DPOAE) levels measured as a function of stimulus level. When the levels of the two stimulus tones (f1 and f2) are related by the formula L1 = 39 dB + 0.4 x L2 [Kummer et al., J. Acoust. Soc. Am. 103, 3431-3444 (1998)] the shape of the function relating DPOAE level to L2 is similar (up to an L2 of 70 dB SPL) to the classic Fletcher and Munson [J. Acoust. Soc. Am. 9, 1-10 (1933)] loudness f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0
10

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 30 publications
6
58
0
10
Order By: Relevance
“…Dorn et al ͑2001͒ fitted an ad-hoc equation to median I/O functions from 77 subjects and observed some of the same trends with frequency, HL, and stimulus level as reported in the present study. Neely et al ͑2003͒ noted the similarity in the shape of the average DPOAE I/O functions for normal-hearing ears with the shape of the loudness function described by Fletcher and Munson ͑1933͒. However, the logarithmic function that successfully characterized both DPOAE growth and loudness growth in that study failed to fit individual DPOAE I/O functions.…”
Section: Discussionmentioning
confidence: 60%
“…Dorn et al ͑2001͒ fitted an ad-hoc equation to median I/O functions from 77 subjects and observed some of the same trends with frequency, HL, and stimulus level as reported in the present study. Neely et al ͑2003͒ noted the similarity in the shape of the average DPOAE I/O functions for normal-hearing ears with the shape of the loudness function described by Fletcher and Munson ͑1933͒. However, the logarithmic function that successfully characterized both DPOAE growth and loudness growth in that study failed to fit individual DPOAE I/O functions.…”
Section: Discussionmentioning
confidence: 60%
“…This reduction in DPOAE level is usually accompanied by elevation of audiometric thresholds (e.g., Boege and Janssen, 2002;Gorga et al, 2003) and loss of compression. In a healthy cochlea, DPOAEs grow approximately linearly with level at low levels, but growth becomes more compressive as levels increase (e.g., Neely et al, 2003). This normal compressive characteristic manifests as a DPOAE I/O function with slope that is steeper at low levels compared to high levels, when the primary levels are selected using the paradigm of Kummer et al (1998).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral measures of cochlear compression based on OAE have been shown to be correlated with growth of loudness Muller and Janssen, 2004;Epstein and Florentine, 2005;Epstein and Silva, 2009;Thorson et al, 2012). Neely et al (2003) showed that the Fletcher and Munson (1933) log-loudness function and DPOAE I/O can both be described by similar log functions. Muller and Janssen (2004) demonstrated the similarity of estimates of hearing-aid gain based on DPOAE I/O functions to gain based on CLS functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At its maximum, the compression ratio estimated from DPOAE I/O functions is approximately 4:1, at least for mid and high frequencies. In previous work, we have estimated the range of input levels over which compression takes place and the amount of compression in both normal and impaired ears (Dorn et al, 2001;Neely et al, 2003). Both the amount of compression and the range of input levels over which compression was observed decreased as hearing loss increased.…”
Section: Introductionmentioning
confidence: 99%